The Evolution of Electricity Markets in Europe - Meeus, Leonardo (Loyola de Palacio Series on European Energy Policy, 2020)
Bridging theory and practice, this book offers insights into how Europe has experienced the evolution of modern electricity markets from the end of the 1990s to the present day. It explores defining moments in the process, including the four waves of European legislative packages, landmark court cases, and the impact of climate strikes and marches.